2021
DOI: 10.1063/5.0064299
|View full text |Cite
|
Sign up to set email alerts
|

Role of local chemical fluctuations in the melting of medium entropy alloy CoCrNi

Abstract: Medium- to high-entropy alloys are characterized by fluctuations in chemical composition, i.e., lattice distortion (LD) and chemical short-range ordering (CSRO). However, their roles in the melting of these alloys are still unclear. Using a combination of molecular dynamics and x-ray diffraction simulations, we investigate the effects of LD and CSRO on the melting of single crystalline CoCrNi, a medium entropy alloy (MEA). LD accelerates the melting process and reduces the melting temperature by lowering the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Because it homogenizes the lattice, SRO usually decreases the average lattice distortion in CCMs 76 . The reduction of lattice distortion usually results in a decreased availability of nucleation sites for new phases or defects, and this, in turn, may increase the melting temperature 92 or affect solid-solid phase transitions, for example.…”
Section: Stacking Fault Energymentioning
confidence: 99%
“…Because it homogenizes the lattice, SRO usually decreases the average lattice distortion in CCMs 76 . The reduction of lattice distortion usually results in a decreased availability of nucleation sites for new phases or defects, and this, in turn, may increase the melting temperature 92 or affect solid-solid phase transitions, for example.…”
Section: Stacking Fault Energymentioning
confidence: 99%
“…Of importance to plasticity studies, the potential is well characterized in terms of the energetics of the stacking faults (89). Since its introduction, the potential has been extensively used for studying the CrCoNi alloy (48,(90)(91)(92)(93), including the effects of lattice distortion and chemical short-range order on the deformation mechanisms of the CrCoNi alloy under shock loading (63,94).…”
Section: Simulationsmentioning
confidence: 99%
“…At an low impact velocity, dislocation slip and twinning dominate and amorphization does not happen, but as the impact velocity increases, the deformation mechanism shifts from slip and twinning to solid-state amorphization [42]. In addition, LD accelerates the melting process and reduces the melting temperature by lowering the energy barrier of the nucleation of amorphous clusters and then promoting the formation of amorphization [43]. Wang et al [44] found that higher impact velocity nucleate more voids followed by a fast void growing and coalescence and also resulting in higher temperature increment.…”
Section: Mechanical Property Analysismentioning
confidence: 99%